Energy consumption, economic growth and CO2 emissions in Middle East and North African Countries - Mohamed El Hedi Arouri; Adel Ben Youssef; Hatem M'Henni; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2012)
This article extends the recent findings of Liu (2005), Ang (2007), Apergis et al. (2009) and Payne (2010) by implementing recent bootstrap panel unit root tests and cointegration techniques to investigate the relationship between carbon dioxide emissions, energy consumption, and real GDP for 12 Middle East and North African Countries (MENA) over the period 1981-2005. Our results show that in the long-run energy consumption has a positive significant impact on CO2 emissions. More interestingly, we show that real GDP exhibits a quadratic relationship with CO2 emissions for the region as a whole. However, although the estimated long-run coefficients of income and its square satisfy the EKC hypothesis in most studied countries, the turning points are very low in some cases and very high in other cases, hence providing poor evidence in support of the EKC hypothesis. Thus, our findings suggest that not all MENA countries need to sacrifice economic growth to decrease their emission levels as they may achieve CO2 emissions reduction via energy conservation without negative long-run effects on economic growth.
Keywords: Q43; Q53; Q56; 330; Environmental Kuznets Curve; carbon dioxide emissions; energy consumption; growth; Kohlendioxid; Luftverunreinigung; Energiekonsum; Sozialprodukt; Environmental Kuznets Curve; MENA-Staaten